Hydrodynamics of viscous slug flow in inclined pipes - Dafyak, Longtong (2023)
Slug flow is the most persistent and challenging gas-liquid flow pattern. Its intermittent and transient nature makes it complex to understand and difficult to model. A detailed review of the literature revealed that existing studies are mainly for air-water mixtures in either horizontal or vertical pipes. However, the flow of various gas-liquid mixtures via pipelines in uneven terrains finds major application in several industrial processes. Therefore, the objective that guides this study is to understand slug flow behaviour and its characteristics for viscous fluids in inclined pipes. This was achieved by investigating the effect of gas velocity, liquid velocity, pipe inclination and liquid viscosity on slug flow parameters. An experimental study was carried out in a 67 mm ID and 6 m long pipe for air-silicone oil mixtures across different pipe inclinations. Electrical Capacitance Tomography (ECT) and High-Speed Camera (HSC) were used to measure the void fraction and capture the flow behaviour of the gas-liquid mixtures respectively. In this study, key aspects of gas-liquid flow in pipes were addressed but the focus was mainly on slug flow parameters and its physical mechanisms. For all the flow patterns identified from the experimental study, the influence of flow variables on the flow patterns and mean void fraction was analysed. The results demonstrated that flow patterns are more susceptible to changes in gas velocity and pipe inclination compared to changes in liquid velocity and viscosity. In terms of the mean void fraction, the effect of gas and liquid velocities depends on the flow pattern whereas it is moderately affected by the viscosity and pipe inclination. A correlation based on the drift flux model was proposed which outperforms most existing semi-mechanistic models by at least 15%; having a root mean square, average percentage, average absolute percentage errors of 0.03 and 0.7% respectively. Subsequently, slug flow was distinguished from other intermittent flow patterns and the effect of flow variables on slug flow parameters was investigated. Out of the 985 experiments conducted, 748 were observed to be either stable or unstable slug flow. Experimental observations showed that the slug frequency, length and void fraction of the slug structures are all significantly influenced by the pipe inclination. Furthermore, the extent to which the superficial velocities and liquid viscosity affect the slug flow parameters varies; some slug parameters are evidently affected by the velocities and/or viscosity whereas some parameters remain unchanged. One of the main contributions of this study is utilizing the void fraction in the liquid slug and HSC images to analyse bubble entrainment mechanisms in inclined pipes. Experimental and theoretical techniques were employed to analyse slug velocity and its components. The experimental study showed that the components of the structure velocity depend on the pipe inclination and liquid viscosity. A theoretical model for the distribution coefficient was proposed. The distribution coefficient,